2022
DOI: 10.1111/dpr.12645
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccination: Willingness and practice in Bangladesh

Abstract: Motivation Mass adult immunization for COVID‐19, coupled with the urgency, is a challenge for any lower‐middle‐income country (LMIC) like Bangladesh. Our analysis focuses on demand‐side constraints early in the vaccination campaign to help gauge vaccine acceptability and potential contributing factors. Identifying registration and compliance challenges early on will help ensure a seamless immunization programme. Purpose We seek to identify subgroups who may need specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A survey in Germany showed that trust in the medical establishment impacts the intention to receive the COVID-19 vaccine [ 58 ]. Confidence in public service delivery also leads to favorable responses to mass immunization efforts [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey in Germany showed that trust in the medical establishment impacts the intention to receive the COVID-19 vaccine [ 58 ]. Confidence in public service delivery also leads to favorable responses to mass immunization efforts [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confidence in public service delivery influenced favorable responses to mass immunization efforts [59]. In summary, when formulating a vaccination plan, we should pay attention to early promotion and publicity, such as the necessity, safety, effectiveness, and other related information of the vaccine.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Around the same period, the French government changed the rule that second jabs must be given same place as the first, allowing holidaymakers to have access to COVID vaccines wherever they were in the country, including beaches and tourist spots. 1 Walk-in vaccination schemes or sessions were envisaged in various countries, from the UK to Bangladesh (Faruk & Al Quddus, 2023 ). In a similar vein other countries, such as Switzerland, the UK and Ireland, allowed local community pharmacists to administer the COVID-19 vaccine, assuming that both proximity and trust would have a positive effect on people's willingness to vaccinate (Paudyal et al, 2021 ).…”
Section: The Ladder Of Intrusivenessmentioning
confidence: 99%